Treatment Domestic Wastewater Using UASB and DFAF Two Phase Combined Reactor Systems: Preliminary Study - Kadir, M.A.A.; Latiff, A.A.A.; Daud, Z. (Journal of Engineering and Technology (JET), 2015)
Anaerobic wastewater treatment technology has shown high organic removals as well as cost-effective processes. This paper presents an evaluation of the feasibility of employing Up-flow Anaerobic Sludge Blanket (UASB) reactor followed by Down-flow Aerobic Filter (DFAF) treating domestic wastewater. Besides, the performance of using zeolite and coconut shell activated carbon as support material will also be appraise. The microbial communities that are responsible of nutrient removal were identified. An analytical study carried out to evaluate the performance of combined UASB (R1, R2, and R3) and DFAF (S1, S2, and S3) reactors in sequence operation. 6.36L UASB reactor seeded with sludge from domestic sewerage plant anaerobic pond to be fed with domestic wastewater. The effluent of UASB reactor directly discharges to the DFAF reactor of 2.84L capacity. The DFAF is a down-flow filter through pack of zeolite and coconut shell activated carbon respectively. The wastewater is fed continuously with increasing OLR until the reactor failed. Parameters measured are pH, and COD. The instruments used for collecting data in this research are pH meter and HACH DR5000. In this research, the highest COD removal for the effluents from the R1, R2 and R3 were at the 12th day with 95% removal at 16th day with 96% and 14th day with 95% respectively. Meanwhile, in the post-treatment system, the highest COD removal for the effluents from the S1, S2 and S3 were at the 4th day with 85% removal at 6th day with 70% removal at the 6th day with 93% removal. The findings of this study would hopefully contribute to the enhancement of current established system in treating domestic wastewater.